Municipal autonomy in brazilian federative context - Santos, Angela Penalva (2012)
The purpose of this article is to analyze the historical and institutional context in which the autonomy of municipal governments is situated within the Brazilian federative sphere. The 1988’s Brazilian Federal Constitution treats the municipality as a “federative entity” with political, legislative, administrative, and financial autonomy. However, the new institutional design provoked reactions that jeopardized such autonomy, especially the financial one. In order to evaluate such reactions, this research analyzed Amendments to the Constitution that somehow affected the municipal autonomy over the last 23 years, in which the current Constitution is in force. Statistics on some municipal financial indicators were presented to situate the impacts of the constitutional reforms. The analysis of the facts suggests that the 1990s were marked by an attack to the financial autonomy of the municipalities, which were considered federative entities somewhat committed to the fiscal adjustment in the economic crisis context. During the following decade, the interfederative cooperation increased, even with the expansion of governmental transfers to the Municipalities. Though, problems arising from tripartite federal structures, marked by a strong heterogeneity between Brazilian municipalities, still have to be solved.